TRANSFORMAÇÕES NO JORNALISMO CIENTÍFICO BRASILEIRO: A PANDEMIA E SEU IMPACTO ENTRE JORNALISTAS E CIENTISTAS - Silva, Thalita Mascarelo da (2021)
The journalistic field has been impacted by internal and external transformations, mainly due to the constant techno-social and economic transitions of this century. The covid-19 pandemic changed the programmed path of this study, further highlighting the